(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Snake poison causes death and tissue disfiguration among the rural people. Though anti-dote or anti-snake venom serum is freely accessible at government health care facilities but is hampered by poor handling, storage and lack of specificity. The necessity of the hour is to find new anti-dotes which are not only inexpensive but can work against a broad variety of snake venoms. In India, most of the poisonous snakes belong to the Elapidae & Viperidae families. In this study, venom of the Flavonoids has been found to have anti-snake venom action owing to which the cabbage was chosen for its high flavonoid content. For this, initially the effective concentration of the Russell’s viper was found on goat’s plasma at 4.54 g/mL and the aqueous extract of cabbage was observed to inhibit proteolysis. Next, the minimal coagulant dosage (MCD) was estimated as 3.69 µg/ml for goat’s plasma and the aqueous extract of cabbage was found to delay venom induced plasma clotting. An examination of these findings suggest that cabbage may be utilized a source of anti-snake venom.